STUDI KELAYAKAN SARANA DAN PRASARANA BENGKEL TEKNIK KENDARAAN RINGAN DI SMK MUHAMMADIYAH MLATI SLEMAN SEMESTER GENAP TAHUN AKADEMIK 2020/2021: Studi Kelayakan Sarana dan Prasarana Bengkel Teknik Kendaraan Ringan di SMK Muhammadiyah Mlati Sleman Semester Genap Tahun Akademik 2020/2021 - fahdzil muhammad tegar perkasa; S Subagyo; Diana Ratnawati (JURNAL VOKASI DEWANTARA (JVD), 2022)
The purpose of this research is to find out the feasibility level of facilities and infrastructure of light vehicle engineering workshop in the light vehicle engineering expertise program at SMK Muhammadiyah Mlati Sleman based on the standards required by Permendiknas RI No. 40 year 2008. This research is a descriptive research, respondents in this study are the head of department and teacher of light vehicle engineering skills program, and infrastructure in the workshop of light vehicle engineering, especially reviewed from the workshop building of light vehicle engineering, workshop of light vehicle engineering, workshop equipment of light vehicle engineering, education media workshop of light vehicle engineering, and other devices workshop of light vehicle engineering in the light vehicle engineering program SMK Muhammadiyah Mlati Sleman. Data collection method by observation, interview, and documentation. The instrument uses a checklist used in observation with a Rating Scale model assessment scale. The data of facilities and infrastructure obtained then compared with the predetermined standards based on permendiknas RI No. 40 year 2008 on Standards of Facilities and Infrastructure vocational high school / Madrasah Aliyah Vocational (SMK / MAK). Workshop infrastructure shows that the level of atability reviewed from the infrastructure of light vehicle engineering workshop is 90.90% (very feasible). For the level of reach reviewed from the workshop facilities of light vehicle engineering is 89.28% (Very feasible). And for the overall achiever level of light vehicle engineering workshop facilities is 89.74% (very feasible).